Approximation in the Application of the Integration - Kumar , Nand Kishor; Yadav, Dipendra Prasad (Medha: A Multidisciplinary Journal, 2023)
The current research discusses approximation and application while introducing the idea of integration. This study aims to determine the problem function when its derivatives are available, as well as to examine its application and explore the approximation of the definite integral using the trapezoidal rule. For the purpose of resolving practical issues and examining mathematical models, it is essential to comprehend the notion of integration, its applications, and the application of approximation techniques. For scientists, engineers, and researchers, integration is still an essential tool that helps improve a variety of professions.